Análise dos resultados da Vídeolaringoscopia de Alta Velocidade na avaliação e Reabilitação Vocal - Ualisson Nogueira do Nascimento (2023)
Introduction: Voice is multidimensional and cannot be measured by a single evaluative metric. The development of high-speed imaging technologies used in voice assessment tools dates back to the 1930s. It was only with the advancement in the processing and storage capacity of computers that these technologies took shape to be exploited for commercial purposes. The main feature of high-speed imaging technologies is the ability to record the real vibratory pattern of the vocal folds. It manages to capture images at a rate many times faster than the vibration speed of the vocal folds, with the possibility of performing cycle-by-glottic cycle analyses. At the end of the 1990s, videokymography was developed as a cheaper, more practical and easier-to-use tool in the clinical environment compared to other high-speed technologies. Its advantage was the possibility of registering a horizontal line of the glottis at up to 7200 frames per second. This allowed another level of analysis of the free edge of the vocal folds. At the beginning of the 21st century, high-speed videoendocopy was commercially available with the potential not only to overcome the technical limitations of videolaryngostroboscopy, but also to advance quantitative analyses derived from its videos. High-speed videoendoscopy provides the possibility of recording high-speed color videos at a rate of up to 10,000 frames per second. In this context, digital videokymography has been developed; a videokymographic evaluation, which analyzes high-speed videoendoscopy videos, opens the door to new possibilities in the diagnostic evaluation of the larynx. Objective: The purpose of this study is to investigate the glottic characteristics of dysphonic individuals undergoing evaluation and vocal rehabilitation based on qualitative and quantitative parameters measured during high-speed videoendoscopy. Methods: Quantitative study approved by the Research Ethics Committee of UFMG-COEP, under the numbers CAAE 44848115.0.0000.5149 and 59014916.6.0000.5149. Three papers are presented as part of the thesis: The first manuscript, perceptual-visual assessment of the glottic characteristics of vocal nodules using high-speed videoendoscopy, was a descriptive observational study using a convenience sample of five laryngeal images of women with a mean age of 25 and diagnosis of vocal nodules. Two otorhinolaryngologist judges agreed 100% intra-rater and 53, 40% inter-rater. An adapted protocol was followed by five otolaryngologists to evaluate the laryngeal images. Statistical analysis was used to calculate central tendency, dispersion, and percentage. The AC1 coefficient was calculated to analyse agreement. The second manuscript, Evaluation of Comprehensive Voice Rehabilitation Program results associated with transcutaneous electric nerve stimulation using digital videokymography in female singers with dysphonia, aimed to evaluate the effects of the Comprehensive Voice Rehabilitation Program with Transcutaneous Electrical Nerve Stimulation in dysphonic female singers through Digital Kymography. This was an intra-subject’s comparative experimental study with twenty-four female singers underwent vocal therapy with Comprehensive Voice Rehabilitation Program associated with Transcutaneous Electrical Nerve Stimulation. High-speed videoendoscopy was performed before and after rehabilitation. Paired T-Test and Wilcoxon test were used to compare the assessments. The significance level was set at 5%. The third manuscript, Analysis of the immediate effects of the LaxVox® technique on digital videokymography parameters in adults with voice complaints, investigated the immediate effects of the LaxVox® technique on digital videokymographic parameters obtained through high-speed videoendoscopy in adults with voice complaints, was an intrasubject, comparative study of adults with voice complaints. Image processing software was used to analyze the videos and obtain digital videokymography parameters. The intraclass correlation coefficient was used to determine the intra-rater reliability of the analyzed parameters. The paired t-test and Wilcoxon signed-rank test were used to compare digital videokymography parameters before and after the LaxVox® technique, in sex-specific analyses. The significance level was set at 5%. Results: The first manuscript examined the vocal nodules in high-speed videoendocopy in order to evaluate their perceptive-visual characteristics. The high-speed videoendocopy of vocal nodules revealed mucosal wave and amplitude ranging from 50% to 60%. There are few non-vibrating portions of the vocal folds, and the glottic cycle is symmetrical and periodic and does not have a phase predominance. Glottic closure is characterized by the presence of a medium-posterior triangular chink (double chink or isolated medium-posterior triangular chink), with no movement of supraglottic structures, with an irregular outline of the free edge of the vocal folds, and these are vertically levelled. According to the results of the second manuscript, significant differences were identified for the parameters of maximum opening, dominant amplitude of the opening variation and dominant frequency of the opening variation of the right vocal fold in the posterior region of the glottis, and for the parameters of maximum opening, mean opening, dominant amplitude of the opening variation of the left vocal fold and dominant frequency of the opening variation of both vocal folds in the anterior region of the glottis. It was concluded that. As a result of the third manuscript, in total, 25 laryngeal images from 15 women and 10 men were analyzed. On digital videokymography analysis, the mean vocal fold opening in the posterior glottal region was decreased immediately after using the LaxVox® technique in women. In contrast, no significant changes were found in the posterior, middle, or anterior glottal regions in men. Conclusion: High-speed videoendoscopy is a promising tool for clinical diagnosis and therapeutic management. The vocal nodules evaluated by the high-speed videoendoscopy have a medium-posterior triangular chink, irregular free edge, and partially reduced mucosal wave and amplitude movement. Using the evaluation of high-speed videoendoscopy, digital videokymography can be used to quantify changes in the vibratory pattern of the vocal folds after vocal rehabilitation for dysphonic individuals. In conclusion, digital videokymography analysis suggests that the Comprehensive Voice Rehabilitation Program with Transcutaneous Electrical Nerve Stimulation promotes a decrease in maximum opening, opening amplitude of the right vocal fold and an increase in frequency of the right vocal fold in posterior region of the glottis, and a decrease in maximum opening, mean opening, amplitude of the left vocal fold and an increase in frequency of both vocal folds in anterior region of the glottis; and revealed that the LaxVox® technique reduces the mean vocal fold opening in the posterior glottal region of women with voice complaints. Future research should consider systematizing laryngeal parameters that are more sensitive to evaluation via high-speed videoendoscopy and digital videokymography that have clinical relevance for speech therapy and otorhinolaryngology.